Non-invasive Investigation of Tumor Metabolism and Acidosis by MRI-CEST Imaging - Consolino, Lorena; Anemone, Annasofia; Capozza, Martina; Carella, Antonella; Irrera, Pietro; Corrado, Alessia; Dhakan, Chetan; Bracesco, Martina; Longo, Dario Livio (Frontiers in Oncology, 2020)
Altered metabolism is considered a core hallmark of cancer. By monitoring in vivo metabolites changes or characterizing the tumor microenvironment, non-invasive imaging approaches play a fundamental role in elucidating several aspects of tumor biology. Within the magnetic resonance imaging (MRI) modality, the chemical exchange saturation transfer (CEST) approach has emerged as a new technique that provides high spatial resolution and sensitivity for in vivo imaging of tumor metabolism and acidosis. This mini-review describes CEST-based methods to non-invasively investigate tumor metabolism and important metabolites involved, such as glucose and lactate, as well as measurement of tumor acidosis. Approaches that have been exploited to assess response to anticancer therapies will also be reported for each specific technique.